2013
DOI: 10.1063/1.4832857
|View full text |Cite
|
Sign up to set email alerts
|

Locomotion of a flapping flexible plate

Abstract: The locomotion of a flapping flexible plate in a viscous incompressible stationary fluid is numerically studied by an immersed boundary-lattice Boltzmann method for the fluid and a finite element method for the plate. When the leading-edge of the flexible plate is forced to heave sinusoidally, the entire plate starts to move freely as a result of the fluid-structure interaction. Mechanisms underlying the dynamics of the plate are elucidated. Three distinct states of the plate motion are identified and can be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
104
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 76 publications
7
104
1
1
Order By: Relevance
“…Experiments with flexible oscillating plates [8][9][10][11][12][13][14][15], two-dimensional [16,17], and three-dimensional computational studies [18][19][20] have provided further insights on thrust production, cruising velocity, and efficiency in a wide parameter space. These studies indicated that fast swimming and larger thrust are related to resonance oscillations.…”
Section: Introductionmentioning
confidence: 98%
“…Experiments with flexible oscillating plates [8][9][10][11][12][13][14][15], two-dimensional [16,17], and three-dimensional computational studies [18][19][20] have provided further insights on thrust production, cruising velocity, and efficiency in a wide parameter space. These studies indicated that fast swimming and larger thrust are related to resonance oscillations.…”
Section: Introductionmentioning
confidence: 98%
“…These three parameters were chosen because they encompass much of the variation in fish swimming kinematics based on previous studies of live fish locomotion (e.g. Bainbridge, 1958;Donley and Dickson, 2000;Webb, 1975), and because prior studies of swimming flexible foils suggested that length and stiffness were key parameters governing locomotor dynamics Hua et al, 2013;Long et al, 1994). Although swimming foils of rectangular shape represent a considerable simplification of the complex three-dimensional geometries of fishes and ignore features such as tail structure, we focus here on the stiffness and length Undulatory locomotion of flexible foils as biomimetic models for understanding fish propulsion Ryan M. Shelton*, Patrick J. M. Thornycroft and George V. Lauder ‡ properties of swimming foils compared with fishes (maintaining uniform thickness and flexibility along the length), and future studies could extend the approach taken in this paper to more complex and fish-like flexible surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the 3D effects on the translational locomotion of a passive heaving wing have been investigated [15]. However, the most previous studies of the locomotion of flapping flexible plate mainly focus on the 2D model [9,16,17]. Therefore, the propulsive performances of the 2D and 3D flexible plates are desirable to be studied.…”
mentioning
confidence: 98%
“…The wings and fins have complex behaviors which are associated with the distribution of the compliant components [1,4] and can deform passively in response to fluid forces [5][6][7][8]. The deformations in turn affect the propulsive performances [9]. In reality the role of flexibility in the flapping-based locomotion is still completely unclear and is of great interest for future detailed studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation